Development of the 3D printing market and its application in medicine - Haberla, Marcin (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
According to forecasts and predictions by leading analyst firms, several million 3D printers were expected to be sold annually by 2020, with consumer devices in virtually every home being the driving force.This article aims to conduct a systematic literature review (SLR) of various applications of 3D printing in medicine. The author based his considerations on Polish and foreign literature, studying scientific articles and electronic sources. The analysis included a review of literature and online sources from 2012–2023. The author used the following professional, academic databases to gather scientifi c literature: Library of Science, Google Scholar, ScienceDirect, Emerald, Emis Intelligence, Passport, and Statista. This article defi nes the concept of 3D printing, presents the development of the 3D printing market, and indicates market trends and applications of 3D printing in medicine. The analysis made it possible to determine the extent of the phenomenon and to identify the main trends that are observed in the field and environment studied.
Keywords: 3D printing; 3D printing market; 3D printing application in medicine